One Pesantren One Product and Economic Resilience During Covid-19 Pandemic: Formulating the Prototype of Independent Pesantrenpreneurs - M. Faisol; Thoyib, Muhammad Edy; Huda, Miftahul (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
The Covid-19 pandemic significantly impacted the economic and educational sectors of Islamic boarding schools. This was particularly due to their perceived lower economic resilience. Therefore, this study aimed to develop a prototype to encourage the establishment of independent pesantrenpreneurs in Indonesia. A descriptive qualitative approach was used to examine the implementation of the One Pesantren One Product (OPOP) program in both mentor and fostered pesantrens. The paradigm of the study followed an interpretive-constructivist framework. The results showed that the success of the Al-Ittifaq Islamic Boarding School in West Java and the Mukmin Mandiri Islamic Boarding School in East Java in managing the pesantrens business could be attributed to several key factors, namely (1) Islamic boarding schools offered superior quality products that aligned with market segmentation, (2) Pesantrens had official and professionally managed business entities, and ensured accountability, (3) A strong network of strategic partners supported the business continuity of pesantrens, (4) The schools adopted creative and innovative approaches to business management, product development, and marketing, (5) Consistent adherence to sharia principles ensured the halalness of products and the incorporation of Islamic values ​​into business processes.